2020
DOI: 10.1123/tsp.2019-0014
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded-Theory Study of Meta-Attention in Golfers

Abstract: This study sought to construct a theoretical understanding of meta-attention in golfers. Eight male golfers (7 competitive-elite and 1 successful-elite) were interviewed about their experiences of attentional processes in competitive golf. A Straussian grounded-theory approach was used throughout the research process, and interview transcripts were analyzed using open, axial, and selective coding. Results indicated that meta-attention is resource based, with metacognitive reflections of logistic and shot resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Compared to previous research that has examined the sequence of cognitions in golf (Calmeiro & Tenenbaum, 2011;Oliver et al, 2020aOliver et al, , 2020b, findings in the current study offer a more advanced and, in some instances, alternative perspective. Using an analytical framework generated in a previous career-based interview study (Oliver et al, 2020b), Oliver et al (2020a) categorised TA data reported by golfers in terms of: attentional metacognitions; control stage; and game situation. Although this categorisation approach is useful for distinguishing the types of cognitions reported, it is plausible to suggest that there was a lack of clarity as regards when these cognitions occur.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Compared to previous research that has examined the sequence of cognitions in golf (Calmeiro & Tenenbaum, 2011;Oliver et al, 2020aOliver et al, , 2020b, findings in the current study offer a more advanced and, in some instances, alternative perspective. Using an analytical framework generated in a previous career-based interview study (Oliver et al, 2020b), Oliver et al (2020a) categorised TA data reported by golfers in terms of: attentional metacognitions; control stage; and game situation. Although this categorisation approach is useful for distinguishing the types of cognitions reported, it is plausible to suggest that there was a lack of clarity as regards when these cognitions occur.…”
Section: Discussionmentioning
confidence: 67%
“…More than two decade ago, McPherson (2000) outlined that studies examining thoughts during actual competition were limited, but this could still be said in the present day. Indeed, much of the literature that has captured data on cognitive processes in sport has done so retrospectively and outside of the task duration (e.g., Brick et al, 2015;Eccles et al, 2002;Oliver et al, 2020a). Furthermore, issues of memory decay and retrospective bias of accounts also pose limitations to using retrospective methods when investigating cognitions (e.g., Folkman & Moskowitz, 2004;Stone et al, 1998).…”
Section: Aloud Methodsmentioning
confidence: 99%
“…To investigate meta-attention further Oliver et al, (2020a) used a grounded theory to understand meta-attention among competitive-elite and successful-elite golfers. The resultant theory showed that meta-attention operated as a bottom-up process with attentional resources evaluated by golfers before using attentional control strategies; selecting an external visual target, implementing a pre-shot routine and a consistent post-shot routine.…”
Section: Metacognition Meta-attention and Its Significance For Understanding Concentrationmentioning
confidence: 99%
“…By understanding their internal and external attentional stimuli athletes can more accurately direct their attentional spotlight and are less likely to succumb to distraction (i.e., illuminating task irrelevant stimuli). Specifically, our current understanding of meta-attention (e.g., Oliver et al, 2020a) shows an evaluation of attentional resources takes place; should an individual experience cognitive anxiety related to their attentional resources their perception of their resource can become an internal distraction. Applying this process to practice, concentration could be enhanced by teaching performers to avoid using binary evaluations of their attentional resources.…”
Section: Teaching Athletes How To Concentratementioning
confidence: 99%
“…These challenges have made golfing performance of particular interest to sport psychologists (McNeill & Meade, 2017). Subsequently, a plethora of research has been conducted surrounding the psychological components impacting a golfer's performance including attentional control (Oliver et al, 2020), motivation (Beauchamp et al, 1996), and choking (Guccuardi et al, 2010) to name a few. Although these psychological components are familiar to other individual skill-based sports, golf offers a completely unique environment as at the highest-level golfers often compete with an assistant, known as a caddie.…”
mentioning
confidence: 99%